Pemanfaatan Media Sosial sebagai Strategi Komunikasi Pemasaran Zumba: Studi pada Akun Instagram @lizanataliaofficial - Putri Ruciraswa Ruwita; Tri Widya Budhiharti; Tikka Muslimah (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to explore the marketing communication strategy used by the Instagram account @lizanataliaofficial in raising public awareness about the importance of Zumba exercise. The research adopts a qualitative method with a descriptive approach and uses the AIDA (Attention, Interest, Desire, Action) model as the theoretical framework. Data were collected through observation, in-depth interviews with six informants, and documentation. The results reveal that @lizanataliaofficial successfully gains attention through engaging and energetic visual content, builds interest with educational information about Zumba, evokes desire by sharing personal experiences and follower testimonials, and prompts action by encouraging followers to participate in Zumba classes and events. This strategy not only increases awareness of the importance of exercise but also fosters an active community on social media. The study indicates that social media can serve as an effective tool for promoting a healthy lifestyle through structured communication strategies.